The effectiveness of demonstrative computer animation in developing intuition: a case for gravitational acceleration - Diyarbekir, Gülşah. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The purpose of this study is to investigate if the gravitational acceleration concept can be intuitively formed in 5th, 6th, 7th and 8th grade students and to investigate the effectiveness of using computer animation technique in the formation of this concept. The design of this study is pretest-treatment-posttest quasi-experimental design. The study is conducted in the first and second semesters of 2005-2006 educational year with the participation of two state schools. The implementation lasted for one hour. The sample of the study is 283 students aging between 11 and 15 years. The subjects were asked to express their estimations about the motion of a flying bird and a free falling apple by locating the positions of the objects at each unit time. After the pretest, the subjects were presented the computer animation which shows the real-event motion of bird and apple. The subjects observed the accelerated motion of apple and constant velocity motion of bird from the computer animation four times, with slower motion each. After the treatment session, the subjects were again asked to locate the positions of apple and bird and to answer the multiple-choice questions related with the motions observed in the computer animation. According to ‘Locate the Position’ pretest results, it is observed that there is a genral tendency among subjects to expect that both objects would move with constant or irregularly changing displacements. According to McNemar test results, it is concluded that the general expectation among subjects have significantly changed in the posttest. It is observed that there is a significant differnce between Orbay P.S. 5. ve 6. grade and Kami Saadet P. S. 6., 7. and 8. grade subjects’ pre and posttest responses in favor of developing intuitive conceptions about gravitational acceleration concept. There is a significant correlation between subjects’ science achievement score and their performance in positioning the apple especially in posttest.
Keywords: Intuition.; Concept learning.